Weight loss during ambulatory tube weaning: don't put the feeds back up. Issue 8 (29th March 2022) - Wright, Charlotte Margaret; McNair, Stephanie; Milligan, Beatrice; Livingstone, Jennifer; Fraser, Emily
Abstract : Objective: To describe the prevalence of weight loss during tube weaning and its impact on wean duration and growth. Setting: Tertiary feeding clinic, UK. Patients: All children seen for weaning from long-term enteral feeding between 2008 and 2016. Interventions: Outpatient withdrawal of enteral feeding. Design: Case series of children being weaned from tube feeding, documenting clinical details, periods of weight loss and timing of feed changes, as well as height and weight at baseline and within 1 year after feed cessation. Main outcome measures: Amount and frequency of weight loss, wean duration, change in body mass index (BMI) and height SD z score. Results: Weaning was attempted in 58 children, median age 2.7 years, and 90% had stopped feeds after median (range) 5.9 (1–40) months. Weight loss was seen in 51 (88%) children and was more common and severe in children with initially higher BMI. Time to feed cessation reduced by median 4.9 months between 2008–2011 and 2012–2016, while having feeds increased prolonged the wean duration, by median 13 months. After feed cessation, mean (95% CI) BMI had dropped by 0.84 (0.5 to 1.2) z scores, but neither change in BMI, nor the amount and frequency of weight loss, related to growth. Conclusions: Short-term weight loss is to be expected during tube weaning and is not associated with compromised growth. It is important to avoid overfeeding enterally fed children and not to increase feeds again in response to weight loss. Abstract : Retrospective case series of outcomes of attempts to stop tube feeding in a cohort of 58 children: take-home message is that weight loss is common during weaning, and if one increases feed rate again, it just takes longer.